2018
DOI: 10.1038/s41598-018-34763-3
|View full text |Cite
|
Sign up to set email alerts
|

Palm Fruit Bioactives modulate human astrocyte activity in vitro altering the cytokine secretome reducing levels of TNFα, RANTES and IP-10

Abstract: Neurodegenerative diseases, including Alzheimer’s disease and Parkinson’s disease, are becoming more prevalent and an increasing burden on society. Neurodegenerative diseases often arise in the milieu of neuro-inflammation of the brain. Reactive astrocytes are key regulators in the development of neuro-inflammation. This study describes the effects of Palm Fruit Bioactives (PFB) on the behavior of human astrocytes which have been activated by IL-1β. When activated, the astrocytes proliferate, release numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 147 publications
(164 reference statements)
0
14
0
Order By: Relevance
“…Coconut oil can protect against neuron differentiation from amyloid toxicity [15]. Additionally, researchers have reported that palm fruit bioactives could modulate the neuroinflammatory events associated with IL-1β-activated human astrocytes in vivo [16]. Declining sensory functions are also common in neurodegenerative disorders, including AD [17].…”
Section: Introductionmentioning
confidence: 99%
“…Coconut oil can protect against neuron differentiation from amyloid toxicity [15]. Additionally, researchers have reported that palm fruit bioactives could modulate the neuroinflammatory events associated with IL-1β-activated human astrocytes in vivo [16]. Declining sensory functions are also common in neurodegenerative disorders, including AD [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that astrocytes are important regulators of CNS inflammatory responses. When activated, they proliferate and release numerous cytokines including TNF-a [27] . In the present study, significant decrease in the mean GFAP area percent associated with decrease in TNF-a gene expression was found in the hippocampal tissue…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that OPP had significantly reduced the protein levels of iNOS and COX-2 as well as inhibited NF-κB subunit p65 in a dose-responsive manner in the LPS-activated cells [55]. Moreover, OPP had significantly reduced the level of inflammatory chemokines such as IP-10, RANTES and TNFα in IL-1β-induced normal human astrocytes [56]. IP-10 is a member of the CXC chemokine family with pro-inflammatory that is involved in the recruitment of Th1 responses [103].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 98%
“…Moreover, OPP had also demonstrated significant reduction in ROS production by IL-1β-activated astrocytes. Additionally, OPP caused reduction in the expression of ICAM and VCAM, both in activated and non-activated human astrocytes [56].…”
Section: Cox-2mentioning
confidence: 98%
See 1 more Smart Citation